Sunteți pe pagina 1din 4

Solution CS161 Spring 12 homework 8

1. Let P(n) be the statement that 13+23+...+n3=(n*(n+1)/2)2 for positive integers n.

a) What is the statement P(1)?

P1) is 13 = ((1*2)/2)2

b) Show that P(1) is true, completing the base of the induction.

13 = ((1.2)/2)2=1

c) What is the inductive hypothesis?

13+23+...+n3=(n*(n+1)/2)2

d) What do you need to prove in the inductive step?

P(n) -> P(n+1) or

13+23+...+n3=(n*(n+1)/2)2 implies 13+23+...+n3+(n+1)3=((n+1)*(n+2)/2)2

e) Complete the inductive step.

(n*(n+1)/2)2 + (n+1)3 = (n2 *(n+1)2 + 4(n+1)*(n+1)2)/4

= ((n+1)2 *(n2+ 4*(n+1))/4


= ((n+1)2 *(n+2)2)/4
= ((n+1*(n+2)/2)2
2) Prove using induction that 1*1! + 2*2! + ....+n*n! = (n+1)! - 1 for any positive
integer n.

a) P(1) is 1*1! = 2!-1

b) Show that P(1) is true, completing the base of the induction.

1*1! = 2!-1
1 =2-1
1 =1

c) What is the inductive hypothesis?

1*1! + 2*2! + ....+n*n! = (n+1)! - 1

d) What do you need to prove in the inductive step?

P(n) -> P(n+1) or

1*1! + 2*2! + ....+n*n! = (n+1)! - 1 implies


1*1! + 2*2! + ....+n*n! +(n+1)*(n+1)! = (n+2)! - 1

e) Complete the inductive step.

(n+1)! - 1 + (n+1)*(n+1)! = (n+2)! - 1


= (n+2)*(n+1)! - 1
=(n+1)*(n+1)! + (n+1)! - 1
1 1 1
3a) Find a formula for   ...  by examining the values of this
1* 2 2 * 3 n(n  1)
expression for small values of n. Follow the format of question 1.

n=1: 1/2 n=2: 1/2 + 1/6 = 2/3 n=3: 2/3 + 1/12 = 3/4 n=4: 3/4 + 1/20 = 4/5

so my formula is

1 1 1 n
  ... 
1.2 2.3 n(n 1) n 1

3b) Prove the formula you found by induction.


 ba) P(1) is 1/2 = 1/2

bb) Show that P(1) is true, completing the base of the induction.

P(1) is obviously true

bc) What is the inductive hypothesis?

1 1 1 n
  ...  
1* 2 2 * 3 n(n  1) n  1

bd) What do you need to prove in the inductive step?

P(n) -> P(n+1) or

1 1 1 n
  ... 
1* 2 2 * 3 n * (n 1) n 1

implies
 1 1 1 n 1
  ... 
1* 2 2 * 3 (n 1) * (n  2) n  2

be) Complete the inductive step.



1 1 1 n 1
  ...    
1* 2 2 * 3 (n  1) * (n  2) n  1 (n  1) * (n  2)

n * (n  2)  1 n 2  2n  1 (n  1) * (n  1) (n  1)
  
(n  1) * (n  2) (n  1) * (n  2) (n  1) * (n  2) (n  2)

S-ar putea să vă placă și